IMF Survey, Volume 32, Issue 14. (IMF Survey; IMF Survey ;, 2003)
In the late 1990s, a series of capital account crises rocked the global economy. The IMF found itself at the center of this turmoil and criticized as never before. The experience triggered extensive internal and external reexaminations of IMF policies and practices and intensified the attention paid by the IMF to identifying vulnerabilities and preventing and resolving crises. It also encouraged the organization to add an external perspective to its learning culture.